Spare parts for fisheries surveillance vessels inventory management in Ministry of Marine Affairs and Fisheries - Velayati, Ema; Karunia, R Luki; Sutrisno, Edy (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to identify problems and formulate a model for managing spare parts inventory of fisheries supervisory vessels in the Directorate of Fleet Monitoring and Operations, Ministry of Marine Affairs and Fisheries to be optimal. The research method is carried out using a qualitative approach. Data collection is done by interviews, field observations and analysis of data and documents. Water inventory management theory (2003) is a theory used to determine the cycle or process of managing spare parts inventory and the Economic Order Quantity (EOQ) method of Horngren (2016) to determine the optimum order quantity and Analysis of ABC Chin (2017) in Putra (2020 to classify inventory into 3 (three) classes, namely A (very important items), B (items that are quite important), and C (relatively unimportant). This study concluded that the management of spare parts in the POA Directorate has not been optimal due to several factors, namely: 1). Human Resources: operators do not have inventory background, and inventory recording with the SAKTI application requires operator involvement, 2). Method: procurement of spare parts is carried out periodically only once a year, so it cannot anticipate changes in needs, and 3), Machinery (Tools): Parts inventory is still done manually with Ms. Excel. Researchers develop a business process model that includes procurement, inventory, storage, delivery, and use of spare parts to improve the efficiency of parts inventory management.